2020
DOI: 10.3389/fchem.2019.00939
|View full text |Cite
|
Sign up to set email alerts
|

Aramid Nanomaterials of Various Morphologies: Preparation and Mechanical Property Enhancement

Abstract: Aramid nanofibers (ANFs) are a novel type of promising nanoscale building blocks for high-performance nanocomposites. Conventionally, ANFs are used to composite with polymers containing polar groups such as-OH and-NH 2 since those polymers can interact with the amide groups in ANFs through polar-polar interaction such as hydrogen bonding. In this study, ANFs were derivatized with non-polar alkyl groups including ethyl, octyl and dodecyl groups and used as a performance-enhancing additive to polyvinyl chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…polyurethane [48][49][50], poly(vinyl alcohol) (PVA) [51], polysulphone [52], polyvinyl chloride [53], and polyamide [54]. Guan et al [53] found that compared with neat PVA, the toughness and tensile strength of PVA nanocomposites with 5 wt % loading of ANFs increased by 149% and 79%, respectively. Nasser et al [54] determined that the tensile strength and elastic stiffness of ANF-reinforced polyamide nanocomposites increased by more than 62% and 27%, respectively, compared to those of neat polyamide.…”
Section: Introductionmentioning
confidence: 99%
“…polyurethane [48][49][50], poly(vinyl alcohol) (PVA) [51], polysulphone [52], polyvinyl chloride [53], and polyamide [54]. Guan et al [53] found that compared with neat PVA, the toughness and tensile strength of PVA nanocomposites with 5 wt % loading of ANFs increased by 149% and 79%, respectively. Nasser et al [54] determined that the tensile strength and elastic stiffness of ANF-reinforced polyamide nanocomposites increased by more than 62% and 27%, respectively, compared to those of neat polyamide.…”
Section: Introductionmentioning
confidence: 99%
“…To further improve the adhesion strength of the ANFs to the matrix material and consequently the mechanical performance of the ANFs, functional groups were introduced on its rigid molecular chain in a variety of ways (Wu and Cheng, 2010 ). The most common approach is surface chemical grafting, in which the functional group is reacted with the amine group on the aromatic ring or the amide bond (Liu et al, 2010 ; Dong et al, 2019 ; Nasser et al, 2019 ). For example, the mechanical properties of aramid fiber were shown to improve with the introduction of amino groups on its surface (Benrashid and Tesoro, 1990 ) or chlorosulfonic acid group on the benzene (Lin et al, 2000 ) ring.…”
Section: Introductionmentioning
confidence: 99%
“…The specific tensile strength data were listed in Table S1. It has been reported that the modified ANFs, in the form of nanospheres, could retain good mechanical properties 19 . It can be speculated that the good mechanical properties of the AEP achieve an effective stress transfer from the cotton fiber to the AEP when tension is introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ANFs have attracted more and more interest. After nanosizing, ANFs still maintain the original high strength characteristics of AFs, and a large number of studies using aramid fibers to enhance the strength of materials have been reported 19–22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation